PENGARUH MOTIVASI, PENGHARGAAN DAN KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU DI SD GLOBAL PRESTASI SCHOOL - Mikhael Christupar; Rudy C. Tarumingkeng (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Teacher performance is a key factor in educational success, yet issues such as tardiness, poor preparation, and low engagement in school activities remain common. This study aims to examine the influence of motivation, rewards, and principal leadership on teacher performance at SD Global Prestasi School. A quantitative approach using Structural Equation Modeling (SEM) was employed, involving 60 teacher respondents. The results show that motivation (p = 0.009; coefficient = 0.421) and rewards (p = 0.011; coefficient = 0.370) have a positive and significant influence on teacher performance. Conversely, principal leadership does not show a significant effect (p = 0.248; coefficient = 0.204). An R-square value of 0.489 indicates that the three variables explain 48.9% of the variance in teacher performance, while a Q-square value of 0.360 demonstrates good predictive relevance. These findings suggest that improving teacher performance should focus on enhancing motivation and providing appropriate rewards.